Students’ Perceptions of using Cake Application for Speaking Skills at The First Grade of SMA Negeri 1 Jambi - Hapipah Hapipah; khidayatul Munawwarah; Kartika Dewi (JELT: Journal of English Language Teaching, 2021)
The objective of the research entitled The Students’ Perception of Using Cake Application for Speaking Skills at the First Grade Students’ of SMAN 1 Jambi this research aim to investigate students’ perception of Using Cake Application for Speaking Skill in findings and discussions, the researcher presents several items of conclusion is follows: The problems of the research is what are students’ perceptions of using Cake application for speaking skills at the first grade of SMA N 1 Jambi. The researcher uses a qualitative research with the use of phenomenology approach. Perception of students in first grade SMAN 1 Kota Jambi which the researcher found in-depth interviews and document analysis. Students’ perception of using Cake Application is very well. This is evident from the students who know what features are available in the cake application which have different functions for speaking skills. By knowing the function of each feature, it proves that students learn and get the benefits and positive effects of the cake application. Lastly students’ perception of using Cake Application for speaking skills is a great application for learning English because English is an international language and learning English can also broaden students’ knowledge of the Indonesian languages than they have learn.Key words: Students’ Perception, Cake Application.